2010
DOI: 10.1074/jbc.m110.142604
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of HemQ

Abstract: Here we identify a previously undescribed protein, HemQ, that is required for heme synthesis in Gram-positive bacteria. We have characterized HemQ from Bacillus subtilis and a number of Actinobacteria. HemQ is a multimeric heme-binding protein. Spectroscopic studies indicate that this heme is high spin ferric iron and is ligated by a conserved histidine with the sixth coordination site available for binding a small molecule. The presence of HemQ along with the terminal two pathway enzymes, protoporphyrinogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 52 publications
7
65
0
Order By: Relevance
“…This idea is consistent with the previously documented interplay of HemY, HemH, and HemQ, where the kinetics of HemH/Y are altered by the presence of HemQ. 24 It could also explain how a catalase positive organism like S. aureus , which avidly detoxifies H 2 O 2 , might be able to manage and use H 2 O 2 as an essential enzyme substrate.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This idea is consistent with the previously documented interplay of HemY, HemH, and HemQ, where the kinetics of HemH/Y are altered by the presence of HemQ. 24 It could also explain how a catalase positive organism like S. aureus , which avidly detoxifies H 2 O 2 , might be able to manage and use H 2 O 2 as an essential enzyme substrate.…”
Section: Discussionsupporting
confidence: 87%
“…Other features typically assigned to vibrations involving the porphyrin pyrrole rings also track the extent of oxidative decarboxylation, including: the increase in ν 7 (pyrrole deformation mode), ν 8 (Fe−N pyrrole stretch), and ν 11 (pyrrole asymmetric folding mode) intensities and the loss in intensity of ν 15 and ν 5 (pyrrole symmetric fold). 20-24 These observations are consistent with changes occurring upon oxidative decarboxylation of propionate groups to yield vinyl substituents.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It is now known that some archaea and sulfate-reducing bacteria synthesize siroheme and then convert it to protoheme (11,42), Gram-positive hemesynthesizing bacteria go through a set of enzymes that utilize a coproporphyrin intermediate (35,(43)(44)(45), and Gram-negative bacteria have a set of enzymes that go through a protoporphyrin intermediate (35). These various pathways to heme in prokaryotes have acquired a variety of common names, such as primitive (46), alternate (11), transitional (43), and classic.…”
Section: Introduction Wmentioning
confidence: 99%
“…Interestingly, the enzyme HemY from Bacillus subtilis has been shown to oxidise both coproporphyrinogen III and protoporphyrinogen IX [12,13]. Further studies reported that a haem-binding protein HemQ that is required for the terminal steps of haem synthesis in species of Actinobacteria and Firmicutes had peroxidase and catalase activity and could stimulate the oxidation of protoporphyrin IX by HemY [14]. S. aureus hemQ mutants were then shown to accumulate coproporphyrin III, and the HemQ enzyme was reported to lyse haem in the presence of peroxide/chlorite [15].…”
Section: Introductionmentioning
confidence: 99%